2018
DOI: 10.17522/balikesirnef.505918
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis for the Effect of GeoGebra on Students’ Academic Achievements in Mathematics

Abstract: This study is a meta-analysis study investigating the effect of the use of GeoGebra software on students' academic achievements in mathematics lessons. With this respect, studies conducted in Turkey were browsed via Council of Higher Education (YÖK) Thesis Center, Turkish Academic Network and Information Center (ULAKBİM) and from database such as Google Scholar. Total of 36 experimental studies and 39 effect sizes were obtained. The sample of this meta-analysis study consisted of a total of 1892 students, 951 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
2
9
0
3
Order By: Relevance
“…This finding is very surprising and contradicts previous predictions that the size of using GeoGebra on the mathematical ability of students in recent years will be larger due to updated software and improved teacher quality. However, about previous findings, the results of this study are consistent with studies conducted by Kaya and € Oçal (2018), Cheung andSlavin (2013), andTamur et al (2020c). The investigators found that the older study group's study effect size was greater than the effect size in the newer study group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is very surprising and contradicts previous predictions that the size of using GeoGebra on the mathematical ability of students in recent years will be larger due to updated software and improved teacher quality. However, about previous findings, the results of this study are consistent with studies conducted by Kaya and € Oçal (2018), Cheung andSlavin (2013), andTamur et al (2020c). The investigators found that the older study group's study effect size was greater than the effect size in the newer study group.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore ( Turgut and Temur, 2017 ), reported an effect size of 0.79 when they analyzed 26 studies comparing computer software use to students' mathematical abilities. Finally ( Kaya and Öçal, 2018 ), reported an effect size of 0.88 when they analyzed 36 studies comparing the use of DGS software on students' mathematical academic achievement in Turkey. Although the number of studies included in this analysis differed from the previous investigators' sample size, this study showed fairly similar software's use points to an overall trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pek çok araştırmada amaca uygun bir şekilde bilgisayar kullanımının öğrencinin matematik yeterliliğini ve okul ortamındaki genel başarısını arttırdığı görülmüştür (Alkan, 1998;Başaran, 1996;Borazan, 2019;Cantürk-Günhan ve Açan, 2016;Çetin, Erdoğan ve Yazlık, 2015;Ersoy, 2003;Kaya ve Öçal, 2018;Wenglinsky, 1998). Öğrenciler bilgisayar destekli bir matematik dersi işlediklerinde bilgiyi keşfetme, anlamlandırma ve görsel olarak pekiştirme deneyimi elde etmektedir.…”
Section: Introductionunclassified
“…Bilgisayar destekli öğretimin, öğrenci başarısını ve kavramsal öğrenmeyi olumlu anlamda etkilediği bilinmektedir(Walter, 2002). Araştırmanın sonuçlardan elde edilen GGB ile ders işlemenin, kavramların öğrenimine olumlu katkı sağlaması, başarıyıarttırması ve öğrenmeyi kolaylaştırması literatürdeki bu sonucu destekler niteliktedir Kaya ve Öçal (2018)…”
unclassified